OFR-23(1)-77 Comparison Of Uniform Four-Foot Length, Fully-Grouted Resin Roofbolts And Alternating Four-And Six-Foot Length, Fully-Grouted Resin Roofbolts ? 1.0 Summary And Conclusions - Joe Maher (The National Institute for Occupational Safety and Health (NIOSH), 1975)
Adequate mine roof support to insure the safety of men and equipment is essential to successful mining. It is also expensive, amounting to more than one-fifth of the total mining cost at the White Pine mine. Cost effectiveness is therefore a prime consideration in developing optimum roof support. Roof bolt length is an important cost factor. This Phase II work compared uniform four-foot length Resin Bolts with the hitherto standard alternating four-foot and six-foot Resin Bolts, aiming at more cost-effective roof bolting. The data generated under this Phase II show that there is no discernible difference in the roof support given by uniform four-foot, and by alternating four- and six-foot, Resin Bolts in the relatively difficult ground selected for a severe initial test comparison; subsequent data from less difficult ground led to the same conclusion, namely no discernible difference between four-foot and four-six foot bolting.